Developing African leafy vegetables for improved nutrition: Regional workshop, 6-9 December 2005 - Oniang’o, R.; Grum, M.; Obel-Lawson, E.; Rural Outreach Program (2008)
The nutritional health value of leafy vegetables has been the main message used to promote increased consumption of them. However, despite the evident importance given to a wide range of leafy vegetables across Africa, the message from the scientific community has not always been clearly positive, with critics focusing on the limited bioavailability of the iron and vitamin A present in them. The preface and several papers in this volume weigh into the debate with reviews, opinions and new research.